Réponses

  • Utilisateur Brainly
2014-09-16T17:10:17+02:00
X/2 - 3 = 4x + 2/3
0,5x - 4x = 2/3 + 3
- 3,5x = 11/3
x = (11/3) : (- 3,5)
x = - 11/3 x 1/3,5
x = - 11/10.5
x = - 22/21

3(2x - 9) = 11 - (2 + 4x)
6x - 27 = 11 - 2 - 4x
6x - 4x = 11 - 2 + 27
2x = 36
x = 36/2
x = 18

5 - 2(4 - 9x) = 1
5 - 8 + 18x = 1
18x = 1 - 5 + 8
18x = 4
x = 4/18
x = 2/9
2014-09-16T17:22:37+02:00

Bonjour

x/2 - 3 = 4x + 2/3
1/2x - 4x = 2/3 + 3
1/2x - 8/2x  = 11/3
-7/2x = (11/3)
x = 11/3  : (-7/2)
x = 11/3 x (-2/7)
x = -22/21

3(2x - 9) = 11 - (2 + 4x)
6x - 27 = 11 - 2 - 4x
6x + 4x = 11 - 2 + 27
10x = 36
x = 36/10
x = 18/5



5 - 2(4 - 9x) = 1
5 - 8 + 18x = 1
18x = 1 - 5 + 8
18x = 4
x = 4/18
x = 2/9